The implementation of integrated learning for developing the entrepreneurship readiness for the students of vocational high school majoring in architecture engineering - V. Lilik Hariyanto; Husaini Usman; Pardjono Pardjono (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
The objective of the research was to: (1) find the level of integrated learning effectiveness between the entrepreneurship subjects and the stone and concrete practical subject from the perspective of the teachers and the students; (2) to find the level of integrated learning implementation between the entrepreneurship subject and the stone and concrete practical subject; (3) to find the level of teacher and student activities within the integrated learning between the entrepreneurship subject and the stone and concrete practical subject; and (4) to find the level of student readiness within the integrated learning between the entrepreneurship subject and the stone and concrete practical subject. The researchers implemented the Research and Development approach with an orientation toward the product development. The research period in the form of learning implementation within the classroom was from January to February 2013. The research site was in 2 Pengasih State Vocational High School Kulonprogo. The research subjects were the students of XI Grade Stone and Concrete Construction Engineering, 2 Pengasih State Vocational High School, Kulonprogo. The research procedures were divided into two stages namely: (1) pre-integrated learning implementation; and (2) integrated learning implementation. The research data included: (1) the effectiveness of integrated learning from the perspective of the teachers and the students; (2) the implementation of integrated learning; (3) the level of activeness that the teachers and the students exposed; and (4) the readiness of the students for performing entrepreneurship based on the achievement of learning competences in the domain of knowledge, attitude and skill. The data analysis was performed in a descriptive-qualitative manner by providing logical narratives according to the research objectives. The results of the research were as follows: (1) the implementation of integrated learning, from the perspective of both the teachers and the students, had been in the category of effective to very effective; (2) the implementation of integrated learning had been in the category of good to very good; (3) the teachers and the students had been in the category of active to very active; and (4) the students had been in the category of ready for performing the entrepreneurship with the achievement of learning scores for more than the already determined passing grade.